Natural history and surgical outcomes for isolated discrete subaortic stenosis in children. Issue 6 (1st December 1999) - Rohlicek, C V; del Pino, S Font; Hosking, M; Miro, J; Côté, J-M; Finley, J
Abstract : OBJECTIVE: To document the natural history and surgical outcomes for discrete subaortic stenosis in children. DESIGN: Retrospective review. SETTING: Tertiary care paediatric cardiology centres. PATIENTS: 92 children diagnosed between 1985 and 1998. MAIN OUTCOME MEASURES: Echocardiographic left ventricular outflow gradient (echograd), and aortic insufficiency (AI). RESULTS: The mean (SEM) age at diagnosis was 5.3 (0.4) years; the mean echograd was 30 (2) mm Hg, with AI in 22% (19/87) of patients. The echograd and incidence of AI increased to 35 (3) mm Hg and 53% (36/68) (p < 0.05) 3.6 (0.3) years later. The echograd at diagnosis predicted echograd progression and appearance of AI. 42 patients underwent surgery 2.2 (0.4) years after diagnosis. Preoperatively echograd and AI incidence increased to 58 (6) mm Hg and 76% (19/25) (p < 0.05). The echograd was 26 (4) mm Hg 3.7 (0.4) years postoperatively, with AI in 82% (31/38) of patients. Surgical morbidities included complete heart block, need for prosthetic valves, and iatrogenic ventricular septal defects. Eight patients underwent reoperation for recurrent subaortic stenosis. The age at diagnosis of 44 patients followed medically and 42 patients operated on did not differ (5.5 (0.6) v 5.0 (0.6) years, p < 0.05). However, the echograd at diagnosis in the former was less (21 (2) v 40 (5) mm Hg, p < 0.05) and did not increase (23 (2) mm Hg) despite longer follow up (4.1 (0.4) v 2.2 (0.4) years, p < 0.05). The incidence of AI at diagnosis and at last medical follow up was also less (14% (6/44) v 34% (13/38); 40% (17/43) v 76% (19/25), p < 0.05). CONCLUSIONS: Many children with mild subaortic stenosis exhibit little progression of obstruction or AI and need not undergo immediate surgery. Others with more severe subaortic stenosis may progress precipitously and will benefit from early resection despite risks of surgical morbidity and recurrence.